PENINGKATAN AKTIFITAS DAN KOOPERATIF SISWA MELALUI PEMBELAJARAN JIG SAW DI SMP NEGERI 1 PREMBUN - Umi Kholifah (IAIN Takengon, 2023)
Jigsaw learning is cooperative type Jigsaw can change the learning atmosphere more effectively and causes students to become more active in seeking and digging various information about the material being explained. This research provides an overview to the reader of the steps for compiling classroom action research. The formulation of the problem in this research discusses How are students' activities in teaching and learning on the concept of Magnetism using the Jig Saw learning method? To what extent can students' cooperative skills be raised in teaching and learning activities that apply the Jig Saw method to the concept of Magnetism? The instrument used in this study was the PTK method from cycle I, cycle II, and cycle III. The research stages used are the planning stage (planning), the implementation stage (acting), the observation stage (observation), and the evaluation stage (reflection). The instruments used were questionnaires and learning observation sheets. Observed learning activities included dependence on listening to (paying attention to) teacher or friend explanations, reading material books/worksheets, working on worksheets, writing (noting) essential material, discussing with friends/teachers, asking friends/teachers and being a presenter. Observed student cooperation was responding to other people's opinions, taking initiatives (turns) and sharing tasks, giving others opportunities to speak, working with friends in groups and students' ability to convey information.